High cholera vaccination coverage following emergency campaign in Haiti: Results from a cluster survey in three rural Communes in the South Department, 2017 - Sharp, Ashley; Blake, Alexandre; Backx, Jérôme; Panunzi, Isabella; Barrais, Robert; Nackers, Fabienne; Luquero, Francisco; Deslouches, Yves Gaston; Cohuet, Sandra (PLOS Neglected Tropical Diseases, 2020)
Author summary After Hurricane Matthew hit Southern Haiti on October 4, 2016, there was an outbreak of Cholera. The Government launched a campaign to vaccinate residents using an oral vaccine, which has been proven to protect people against the disease. MSF supported the campaign in three rural areas, offering the vaccine in local clinics and going from door to door. We didn’t know how many people were living there at the time so we couldn’t say for sure if we had vaccinated enough people. To find out how many people were vaccinated we did a survey, choosing households at random and asking them if and where they received the vaccine. This showed that on average around 90% of people were vaccinated, which is a very high proportion. We can take encouragement from this that mass vaccination campaigns like this can work well, even in rural settings. Our survey showed that about half of people got their vaccine from a clinic and the other half from door-to-door vaccinators, so it’s probably important to use both approaches. Most people heard about the campaign through members of the local community called ‘criers’. This shows how important it is to engage with the local community during a vaccination campaign.